Model Evaluasi Kurikulum Pendidikan Islam di Madrasah dalam Menghadapi Tantangan Era Digital - Asrori, Hilmi (IIQ An Nur Yogyakarta, 2025)
The development of the digital era brings challenges and opportunities for the world of education, including in the Islamic education curriculum in madrasas. This study aims to evaluate the Islamic education curriculum in madrasas in facing the challenges of the digital era and identifying its implementation. The method used in this study is library research by collecting data from books, journals, and related articles. The results of the study indicate that the Islamic education curriculum in madrasas has begun to adapt to the use of digital technology, such as the use of digital-based learning media and online platforms. However, there are still obstacles in implementation, such as limited technological infrastructure, lack of training for educators, and resistance to changes in learning methods. Therefore, continuous evaluation of the Islamic education curriculum is needed to be more responsive to the needs of the times. Recommendations from this study include strengthening digital learning policies, increasing teacher competence in the use of technology, and providing adequate facilities and infrastructure.